2019
DOI: 10.26873/svr-812-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of L. Methionine, L. Carnitine, Choline and/or Silymarin in Hepatoprotection Against Paracetamol Intoxication and Oxidative Stress in Broilers

Abstract: Paracetamol (Acetaminophen) was used for long time in poultry as an antipyretic drug and as a growth stimulator. However, high doses of paracetamol cause unpleasant side effects such as hepatorenal toxicity as mirrored by depletion of glutathione reserve, increase lipid peroxidation and increase liver enzymes or even sudden death with lethal doses. Therefore, this study was designated to evaluate the ameliorative effect of L. methionine, L. carnitine, choline and/or silymarin on the hepatotoxic effect induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The increase in free radicals in cells has been linked to MDA overproduction ( Maurya et al, 2021 ). The results of this study agree with those of Aziz et al (2019) , who reported that dietary supplementation with LC significantly reduced MDA levels in broiler serum and liver ( Aziz et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…The increase in free radicals in cells has been linked to MDA overproduction ( Maurya et al, 2021 ). The results of this study agree with those of Aziz et al (2019) , who reported that dietary supplementation with LC significantly reduced MDA levels in broiler serum and liver ( Aziz et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…The improvement in live body weight, weight gain, and the food conversion factor may be due to the role of choline chloride, as choline is an essential and necessary source for the cell in donating a methyl group that is important for the manufacture of methionine and creatine. [33]; [34] and also choline has an important role in the metabolism and metabolism of liver fats, preventing the occurrence of fatty liver and activating the liver process [16] and choline has a role as an antioxidant and reducing oxidative stress [35]. The reason for the superiority in weight, weight gain, and feed conversion ratio in the first period may be due to the essential amino acid leucine, which activates the synthesis of proteins involved in the structure of muscles by activating the enzyme rapamycin, which is necessary in building skeletal muscles, especially in the early stages of the age of chicks.…”
Section: Resultsmentioning
confidence: 99%
“…However, specifically in the poultry industry, which demands practical and cost-effective solutions, the dose is a critical aspect to be analyzed when determining the efficacy of feed additives ( Surai and Surai, 2023 ). Several authors have tested silymarin effects in ameliorating hepatic damage in broilers and obtained significant improvements in growth performance using doses around 500 mg/kg or higher in the feed ( Khatoon et al, 2013 ; Jahanian et al, 2017 ; Aziz et al, 2019 ). At lower doses, silymarin has a positive influence on productive performance, but when compared with the additive-free diet, the differences are not always statistically significant ( Schiavone et al, 2007 ; Blevins et al, 2010 ; Sakamoto et al, 2018 ; Lukanov et al, 2019 ; Armanini et al, 2021 ; Shanmugam et al, 2022 ; Surai and Surai, 2023 ).…”
Section: Discussionmentioning
confidence: 99%